Impacto del COVID-19 en los establecimientos turísticos de la ciudad de Guaranda: retos y oportunidades para la reactivación económica - Cedeño Velez, Margarita Leticia (2022)
The tourism sector has been affected in recent years by the impact of COVID-19, there were many losses both economic and social. In tourism and especially in tourism establishments, the design of strategies for the enhancement of the same is of utmost importance, in order to meet a highly segmented demand in terms of trends and ways of doing tourism, so the objective of the work focuses on identifying the impacts of COVID-19 and establish strategies for economic recovery, allowing the owners of tourism establishments to manage and create new alternatives that help the early recovery. Therefore, the research carried out aims to contribute in a theoretical and practical way to future research, the total number of establishments surveyed in the urban area of Guaranda is 38, for which the methodology used is a descriptive approach with a qualitative and quantitative scope, with the use of surveys with closed questions to the owners/managers in charge, in order to know the current situation of the tourist establishments. It was concluded that many of them are not in the tourist registry, there were also economic losses, staff cuts and low demand. In this context, several strategies were proposed for the enhancement and positioning of the establishments focused on governance, financing, human resources and marketing.